The Effect of the Composition of Adsorbed Layer at Globule Interface of -3 Fatty Acids Enriched Triglyceride Prior to Spray Drying on its Microcapsule Properties - Teti Estiasih; Moch Adnan; Tranggono Tranggono; Suparmo . (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2005)
Emulsification is the critical factor in microencapsulation by spray drying method. Sodium caseinate is a protein with good emulsifying properties. The properties could be improved by phospholipids addition in the emulsification. Phospholipids addition which stabilized oil globule might change the composition of adsorbed layer. This research was conducted to analyze the changes in composition at oil globule interface by analyzing emulsion systems of triglyceride enriched by -3 fatty acids at 5% (w/v) stabilized by sodium caseinate (10% w/v) and addition of phospholipids at 0; 0,5; 1,0; 1,5; 2,0; and 2,5% (w/v). The changes in composition of adsorbed layer could be determined from the changes in phospholipids and adsorbed protein concentrations at oil globule interface. Analyses were done to measure the possibility of casein-phospholipids complex, phospholipids and protein adsorption concentration at interface, and adsorbed protein. The increase of phospholipids concentration in the emulsions stabilized by sodium caseinate changed the composition of adsorbed layer at interface. There was phospholipids increase and adsorbed protein decrease at oil globule interface. These changes were caused by casein-phospholipids complex which that decreased surface activity and displacement protein by phospholipids that was adsorbed at oil globule interface. Changes of composition of casein-phospholipids at oil globule prior to microcapsulation process caused changes in the properties of microcapsule produced. The increasing phospholipids and decreasing casein concentrations at oil globule interface decreased the quality of the microcapsule, including decreasing in microencapsulation efficiency, in oxidative stability, and decreasing in EPA+DHA content. Key words : Emulsification, microencapsulation, adsorbed layer, surface acitvity, displacement